The effects of wet suits on physiological and biomechanical indices during swimming - De Lucas, Ricardo Dantas [UNESP]; Balikian, Pedro; Neiva, Cassiano Merussi; Greco, Camila Coelho [UNESP]; Denadai, Benedito Sérgio [UNESP] (Elsevier, 2000)
The objectives of this study were to verify the effects of wet suits (WS) on the performance during 1500m swimming (V1500), on the velocity corresponding to the anaerobic threshold (VAT) and on the drag force (AD) as well as its coefficient (Cx). 19 swimmers randomly completed the following protocols on different days (with and without WS): 1) maximal performance of 1500m swimming; 2) VAT in field test, with fixed concentration of blood lactate (4 mM) and 3) determination of hydrodynamic indices (AD and Cx). The results demonstrated significant differences (p < 0.05) in the VAT (1.27±0.09; 1.21±0.06 m.s-1), and in the V1500 (1.21±0.08; 1.17±0.08 m.s-1), with and without WS, respectively. However the AD, and its Cx did not present significant differences (p>0.05) for the respective maximal speeds of swimming. In summary, we can conclude that WS allows swimmers to reach greater speeds in both, long- and short-course swims. This improvement can be related to the decrease of the AD, since with higher speeds (with WS) the subjects presented the same resistance, as they did when compared to speeds without a WS. Moreover, these data suggest that the methodology used in this study to determine the Cx is unable to detect the improvement caused by WS.
Keywords: lactic acid; water; anaerobic threshold; biomechanics; hydrodynamics; lactate blood level; swimming; triathlon; velocity; wettability; Adult; Anaerobic Threshold; Analysis of Variance; Biomechanics; Female; Humans; Lactic Acid; Male; Models, Theoretical; Protective Clothing; Psychomotor Performance; Swimming